Ambulatory Activity of Older Adults Hospitalized with Acute Medical Illness - Fisher, Steve R. (2010)
OBJECTIVES: To describe the amount and patterns of ambulatory activity in hospitalized older adults over consecutive hospital days. DESIGN: Observational cohort study. SETTING: University teaching hospital Acute Care for Elderly (ACE) unit. PARTICIPANTS: Adults aged 65 and older (N = 239) who wore a step activity monitor during their hospital stay. MEASUREMENTS: Total number of steps per 24-hour day. Mean daily steps were calculated based on number of days the step activity monitor was worn. RESULTS: Mean age was 76.6 ± 7.6; 55.1% of participants were female. Patients took a mean number of 739.7 (interquartile range 89–1,014) steps per day during their hospital stay. Patients with shorter stays tended to ambulate more on the first complete day of hospitalization and had a markedly greater increase in mobility on the second day than patients with longer lengths of stay. There were no significant differences in mean daily steps according to illness severity or reason for admission. CONCLUSION: Objective information on patient mobility can be collected for hospitalized older persons. Findings may increase understanding of the level of ambulation required to maintain functional status and promote recovery from acute illness.